This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: A 1 = = A 1 = Proof: We know that A x A1 = X = = Page 256 # 20(b) Find A 3 Given: A = we know that A 3 = A 2 X A A 2 = = = A 3 = Page 256 # 20(c) Find (A1 ) 3 Given: A = we know A 1 = (A 1 ) 2 = x = = (A 1 ) 3 = = Page 256 # 20(d) Use your answers to (b) and (c) to show that (A 1 ) 3 is the inverse of A 3 . We know that & (A —1 ) 3 (A 3 )1 = = (A 3 )1 = = (A 1 ) 3...
View
Full
Document
This note was uploaded on 03/11/2012 for the course LSDHFA 234 taught by Professor Sdaf during the Spring '12 term at UOIT.
 Spring '12
 sdaf

Click to edit the document details